Inter‐country trade, genetic diversity and bio‐ecological parameters upgrade pest risk maps for the coconut hispid Brontispa longissima. Issue 4 (27th November 2019) - Lu, Baoqian; Peng, Zhengqiang; Lu, Hui; Yang, Fan; Lin, Peiqun; Chu, Xiaoqiang; He, Xing; Tang, Jihong
Abstract: BACKGROUND: Invasions of a number of tree‐feeding beetles have increased globally and pose a mounting threat to the world's trees, production forests and natural habitats. An in‐depth understanding of the determinants of invasion potential of a given species and invasibility of novel environments can help forecast future invasions and avert undesirable socio‐economic impacts. Here, we quantitatively assess the (multivariate) drivers of historic invasions of the coconut hispid Brontispa longissima (Coleoptera: Chrysomelidae) across the Asia‐Pacific region and critically assess its invasion potential for other key coconut‐growing regions. RESULTS: Genetic variation of B. longissima in its invaded range indicated multiple incursions, likely associated with (short‐range) natural dispersal and (long‐range) trade in ornamental palms and coconut plantlets. Interception records at China's ports of entry accentuate the role of traded planting material. The high fecundity and prolonged, yet adaptable, oviposition period of B. longissima further enhance the invasiveness of this species and aid its successful establishment. Coconut‐growing areas are identified with high climatic suitability for B. longissima, and where strengthened biosecurity protocols can prevent future invasions. CONCLUSION: A combined assessment of inter‐country trade patterns, population genetics and species bio‐ecology (e.g. climate‐related development) illuminates the dispersal pathways of invasive species, assesses invasibility of particular geographies, guides quarantine interventions and thus can effectively avert future invasions. © 2019 Society of Chemical Industry Abstract : A combined assessment of inter‐country trade patterns, population genetics and species bio‐ecology illuminates the dispersal pathways of the invasive species Brontispa longissima .